2000
DOI: 10.2307/3871037
|View full text |Cite|
|
Sign up to set email alerts
|

Osmotic Stress Induces Rapid Activation of a Salicylic Acid-Induced Protein Kinase and a Homolog of Protein Kinase ASK1 in Tobacco Cells

Abstract: In tobacco cells, osmotic stress induced the rapid activation of two protein kinases that phosphorylate myelin basic protein. Immunological studies demonstrated that the 48-kD kinase is the salicylic acid-induced protein kinase (SIPK), a member of the mitogen-activated protein kinase family. SIPK was activated 5 to 10 min after the cells were exposed to osmotic stresses, and its activity persisted for approximately 30 min. In contrast, the 42-kD kinase was activated within 1 min after osmotic stress, and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 0 publications
5
103
0
1
Order By: Relevance
“…Our previous results concerning NtOSAK of the SnRK2 subfamily (25), the results obtained by the Hattori group on two rice SnRK2s (14), and the very recent ones by Belin et al (26) on Arabidopsis OST1 kinase suggested that these enzymes were activated by phosphorylation. Contrary to this, Hoyos and Zhang (27) claimed that high osmolarity stress-activated kinase from tobacco, whose properties resemble those of NtOSAK, was activated by dephosphorylation.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Our previous results concerning NtOSAK of the SnRK2 subfamily (25), the results obtained by the Hattori group on two rice SnRK2s (14), and the very recent ones by Belin et al (26) on Arabidopsis OST1 kinase suggested that these enzymes were activated by phosphorylation. Contrary to this, Hoyos and Zhang (27) claimed that high osmolarity stress-activated kinase from tobacco, whose properties resemble those of NtOSAK, was activated by dephosphorylation.…”
mentioning
confidence: 75%
“…Purification of NtOSAK-NtOSAK was purified from BY-2 cells treated for 5 min with 250 mM NaCl according to the method described previously (25).…”
Section: Methodsmentioning
confidence: 99%
“…Arabidopsis suspension cultures were grown in Gamborg B5 medium as described by Yamada et al (24); BY-2 cells were grown under conditions described elsewhere (4,25). Cells were subcultured every 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Purification of NtOSAK from Tobacco BY-2 Cells-NtOSAK was purified from BY-2 cells treated for 5 min with 250 mM NaCl according to the method described previously (4,5).…”
Section: Methodsmentioning
confidence: 99%
“…Among three kinases, MAPK has been best characterized in plants, as exemplified by AtMPK3, AtMPK4, AtMPK6 from Arabidopsis, SAMK and SIMK from alfalfa, and WIPK and SIPK from tobacco. [3][4][5][6][7] WIPK (wound induced protein kinase) was originally identified as a wound and pathogen responsive kinase, of which transcripts were induced as early as 10 min after mechanical wounding in both wounded and adjacent unwounded leaves, and considered to play a critical role in stress response in tobacco plants. 8 One of its direct upstream MEKs was shown to be NtMEK2, as its constitutive activation induced WIPK activity together with hypersensitive responsive cell death.…”
Section: Map Kinase Cascadementioning
confidence: 99%